Notification of crop varieties and registration of germplasm : Bread Wheat Variety DBW 107 - Singh, S.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Wheat is one of the major rabi crop in the eastern India. Most of the areas follow rice-wheat cropping system and thus, the delayed harvesting of rice results in delayed sowing of wheat crop. This shorter crop season exposes the wheat crop to heat stress during grain filling period. Terminal heat stress is one of the major abiotic factors that adversely affect the wheat production in the North Eastern Plains Zone (NEPZ). Among biotic stresses, leaf rust and foliar blight are crucial to wheat crop. Thus, there is need of a short duration high yielding wheat genotype with disease resistance and tolerance to terminal heat stress. Keeping this in view, the Crop Improvement division of the IIWBR (earlier DWR), Karnal has developed bread wheat variety DBW 107 which was evaluated and released for commercial cultivation under late sown, irrigated condition of NEPZ.